The Relationship between Creativity and Cognitive Aactions in Design Process - Nazife Asli Kaya; Seniz Cikis (Revista de Arquitectura (Bogotá), 2025)
This research explores the relationship between creativity and cognitive actions in a design process that cause conceptual expansion and shift to understand how creative insights develop. The research was conducted with 25 participants using the think-aloud protocol who were given a design problem to solve. Linkographic entropies were obtained from the verbal data of design sessions to determine critical moves (CM) and their associated design decisions. CM networks were then coded using Function-Behaviour-Structure (FBS) ontology to determine design actions, and semantic analysis was used to determine the design transformation types.